Modulation of immunosuppressive cells and noncoding RNAs as immunotherapy in osteosarcoma - Xia, Yidan; Wang, Dongxu; Piao, Yuting; Chen, Minqi; Wang, Duo; Jiang, Ziping; Liu, Bin (Frontiers in Immunology, 2022)
Osteosarcoma (OS) is the most common bone malignancy and primarily affects children and adolescents. Early surgical resection combined with chemotherapy significantly improves the prognosis of patients with OS. In patients with distant metastases or inoperable resection, available chemotherapies have limited efficacy, and these patients may respond better to new immunotherapies. Immune escape, which is mediated by immunosuppressive cells in the tumour microenvironment (TME), is an underlying cause for the poor prognosis of OS and is a key target of immunotherapy The interactions of immunosuppressive cells in the TME have been shown to promote tumour progression at multiple levels, including tumour-associated macrophages, which promote tumour growth and angiogenesis while inhibiting OS metastasis. The differential expression of noncoding RNAs (ncRNAs) in OS cells supports its regulatory role in the development of OS. Studies on the metabolic characteristics of immunosuppressive cells in the TME, and ncRNAs in OS cells, have provided beneficial insights into the research and development of immunotherapies such as interferon, checkpoint inhibitors, cancer vaccines, and engineered chimeric antigen receptor (CAR-T) T cells for OS. This review summarises the characteristics of ncRNAs in OS cells and the metabolic heterogeneity of immunosuppressive cells in the TME. The diverse mechanisms of action in immunotherapy are analysed, and the differences among the four immunotherapies are compared.